Canonical prolactin signaling and global mRNA expression in the skin of Holstein heifers carrying the SLICK1 allele of the prolactin receptor gene - Montana D. Altman; Alice T. Mathews; Maria B. Rabaglino; Russell C. Hovey; Anna C. Denicol (Journal of Dairy Science)
ABSTRACT: The SLICK1 allele of the prolactin receptor gene is associated with a short hair coat and thermotolerance in cattle. SLICK1 includes a single base pair deletion that creates a premature stop codon and prevents transcription of 120 AA in the cytoplasmic tail of the prolactin receptor (PRLR). It is unknown if the presence of the SLICK1 allele modifies Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling or the transcriptional response to prolactin. To investigate PRLR-associated signaling pathways in heterozygous SLICK1+/− Holsteins (slick), we performed immunohistochemistry on skin explants obtained from slick (n = 5) and nonslick (n = 6) heifers to evaluate phosphorylated (p)STAT1, pSTAT3, and pSTAT5 immunoreactivity (pSTAT1+, pSTAT3+, pSTAT5+) in hair follicles (HF) and sweat glands (SG). In slick skin, more HF lacked pSTAT3 immunoreactivity compared with nonslick skin. No difference was found for the proportion of pSTAT1+ or pSTAT5+ HF, nor the proportion of pSTAT1+ and pSTAT3+ SG between genotypes. Within immunoreactive HF and SG, there were no differences between genotypes in the proportion of pSTAT1+, pSTAT3+, or pSTAT5+ cells in HF, or pSTAT1+ and pSTAT3+ cells in SG. Next, we investigated pSTAT3 immunoreactivity and the transcriptome of slick and nonslick skin explants after exposure to a controlled level of prolactin in vitro. Skin explants from slick (n = 6) and nonslick (n = 6) heifers were cultured for 36 h in the presence of 50 ng/mL of recombinant ovine prolactin, bisected, and each half underwent immunohistochemistry for pSTAT3 or RNA sequencing. No difference was found between genotypes in the proportion of pSTAT3+ HF or SG, nor the proportion of pSTAT3+ cells within HF or SG. RNA was poly-A enriched and sequenced using Novaseq6000 (Illumina) and 221,342,181 reads were mapped to the bovine genome (bosTau 9). Using the DESeq package of R to determine differentially expressed genes (DEG), we found 87 upregulated and 79 downregulated transcripts in slick compared with nonslick skin. Ingenuity Pathway Analysis identified IL-17, leukocyte extravasation, and wound healing as upregulated signaling pathways, as well as activation of TNF, IL-1β, OSM, IFNγ, IL-17α, and IL-1R and inhibition of SHH and BMP4 upstream of the DEG. Analysis of genomic regions within ±2 kb of all DEG respective transcription start sites revealed enrichment of 3 binding sites for the OCT1 transcription factor in slick skin. In conclusion, our results suggest differences in local immune regulation, hair growth inhibition, and tissue remodeling in slick skin.